Analysis of the Level of Social Skills among Educational Personnel:A Field Study in the Educational Institutions of Sebseb Municipality (مجلة الواحات للبحوث والدراسات, 2025)
The present study aimed to analyse the level of social skills among educational personnel in the municipality of Sebseb, Ghardaïa. The investigation encompassed a total population (n = 88) of educational staff—including principals, teachers, and superintendents —comprising 30 males and 58 females, all of whom were assessed via exhaustive sampling. Employing a descriptive research design consonant with the study’s objectives, data were gathered using the Social Skills Scale developed by Nasr-El-Din Abdel-Hamid (2011). Statistical analyses were conducted with the Social Sciences Statistical Package (SPSS), utilising frequency distributions, percentages, arithmetic mean, and standard deviation as primary techniques,results indicated that:• The overall level of social skills among the educational personnel in Sebseb municipality is high.• No statistically significant differences in social skills levels were observed across gender.• No statistically significant differences in social skills levels were observed across age groups.• No statistically significant differences in social skills levels were observed across varying lengths of professional experience.• No statistically significant differences in social skills levels were observed across different workplace settings.• No statistically significant differences in social skills levels were observed across types of educational roles.Keywords: social skills level; educational personnel .